Kidney transplantation for end‐stage renal disease secondary to familial Mediterranean fever. Issue 7 (6th May 2016) - Altindal, Mahmut; Turkmen, Ercan; Yildirim, Tolga; Yilmaz, Rahmi; Aki, Fazil Tuncay; Arici, Mustafa; Altun, Bulent; Erdem, Yunus
Abstract: Although kidney transplantation (KT) is widely used for treating renal amyloidosis secondary to familial Mediterranean fever (FMF), data concerning transplant outcome are limited and inconsistent. The aim of this study was to determine the long‐term outcome of KT in patients with amyloidosis secondary to FMF. Kidney transplantation outcome in 24 patients with FMF was compared to that in 72 controls matched for age, gender of recipient, and type of the donor that underwent KT due to end‐stage renal disease (ESRD) not caused by FMF. Mean follow‐up time was 80.3 ± 55.1 months in the FMF group, vs. 86.5 ± 47.6 months in the control group. Death‐censored graft survival at five and 10 yr in the FMF group was 95.8% and 78.4%, respectively, and was comparable to that in the control group. In the FMF group, five‐ and 10‐yr patient survival (87.5 and 65.6%) was shorter than in the control group, but the difference was not statistically significant. The findings show that long‐term outcome of KT in the patients with amyloidosis secondary to FMF was comparable to that in patients with ESRD not caused by FMF. Recurrence of amyloidosis in the allograft, gastrointestinal intolerance, and fatal infections remain as major complications during the post‐transplant period.